The Effect of Liquid Organic Fertilizer Application on the Growth of Microalgae Chlorella sp. - Lady Ayu Sri Wijayanti; Mochhamad Ikhsan Cahya Utama; Andini Nur Afifah; Annisa Rahmah Septiani; Muhammad Wijatmikko Ginang Pratidnia; Yuyun Yuningsih; Sara Umbekna; Sitty Ainsyah Habibie (Gorontalo State University, 2025)
Microalgae such as Chlorella sp. are valuable for their potential in sustainable food, feed, and bioenergy production, but their cultivation often relies on costly synthetic nutrients. Exploring alternative nutrient sources, such as liquid organic fertilizers, may offer a more economical and environmentally friendly approach to biomass production. This study aims to evaluate the effect of liquid organic fertilizer application on the growth of Chlorella sp. in a closed culture system. Seven treatments were used: one control without fertilizer (K) and six treatments with increasing fertilizer doses (P1–P6). The observed parameters included initial and final cell density, as well as daily growth rate during a seven-day incubation period. The results showed that fertilizer application had a significant effect on the growth enhancement of Chlorella sp. The highest final cell density was recorded in treatment P6, exceeding 6.3 × 10⁷ cells/ml, while a population decline was observed in the control group. The daily growth rate also increased with higher fertilizer doses, with the highest value (μ = 0.36) observed in P6. Linear regression analysis showed a strong relationship between fertilizer amount and growth rate (r = 0.8493; p = 0.0156; R² = 0.7213), indicating that growth variation could be significantly explained by the amount of fertilizer applied. The conclusion of this study is that liquid organic fertilizer has great potential as an efficient and environmentally friendly alternative for microalgae culture media. Proper dosage formulation can support optimal microalgal biomass production. Further research is needed to identify the dominant nutrient content in the fertilizer and to assess the biomass quality for potential applications in food, feed, or bioenergy sectors.